PENGARUH LKPD TERINTEGRASI MATERI GELOMBANG GEMPA BUMI TERHADAP KOMPETENSI FISIKA PESERTA DIDIK DI SMA - Tri Anggun Wahyuni (Universitas Negeri Padang, 2018)
The motivation of learners can be enhanced through contextual and meaningful learning by integrating real problems that exist in the surrounding environment into teaching materials of learners, such as earthquake waves. The purpose of this research is to investigate the difference, influence and contribution of LKPD integrated material of earthquake wave to the competence of learners in CPS type simplex model on wave material in class XI SMA N 2 Padang. This type of research is quasi experiment with randomized control group design only design. The study population is all students of class XI MIPA SMA N 2 Padang. Sampling of research using technique of Purposive sampling. The research data is the data of students learning outcomes knowledge competence, attitudes and skills and the value of integrated LKPD earthquake waves. In order to know the difference of competence of the students, there are two equality test (t test), while to know the influence and contribution of LKPD to the competence of the learner, the regression and correlation test is done on the real level of 0,05 for all the competence.The results of the research through correlation test obtained the value of knowledge rs 0,78, attitude 0,62 and skill 0.73. LKPD's contribution to the knowledge aspect is very strong, with a contribution percentage of 60.49%. LKPD contribution to attitude aspect is strong, with contribution percentage equal to 38,73%. LKPD's contribution to skills aspect is strong, with a contribution percentage of 53.03%.